A Novel System for Yarn Cross-Section Analysis Based on Dual Orthogonal CCD Sensors. Issue 1 (2nd January 2019) - Li, Guanzhi; Akankwasa, Nicholus Tayari; Zhao, Qiang; Wang, Jun
ABSTRACT: As a basis for yarn evenness measurement, a novel method based on two orthogonal charge-coupled device (CCD) sensors has been devised. We present a system for analyzing yarn evenness from the coefficient of variation of yarn perimeter, treating the yarn cross-sectional shape like an ellipse with uneven edges. The system architecture, algorithm flow, mathematical principle, and the experimental validation of the proposed technique are presented. A comparison between the proposed method and the conventional Uster Tester 5 and Lawson-Hemphill was made. Results agree quite well with existing methods hence can be implemented as an alternative technique for yarn evenness quantification.